2016
DOI: 10.3168/jds.2016-10938
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Associations between blood fatty acids, β-hydroxybutyrate, and α-tocopherol in the periparturient period in dairy cows: An observational study

Abstract: The objective of the present study was to examine the relationships between blood concentrations of fatty acids, β-hydroxybutyrate (BHB), and α-tocopherol during the periparturient period in dairy cows. Blood samples were collected from 131 cows belonging to 4 different commercial dairy farms in southeastern Europe (Greece and Italy). We determined blood concentrations of fatty acids, BHB, and α-tocopherol at dry-off, at calving, and 30d postpartum. Results indicated that fatty acid concentrations were low at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Fatty acids (FFA) and b-hydroxybutyrate (BHB) are the two markers used to assess the severity of the negative energy balance. In a previous study including four commercial farms located in Italy and Greece, our group showed that these two markers are not well correlated during the transition period (Pilotto et al 2016). In fact, the concentration of free fatty acids in blood became maximal during calving and declined postpartum, while BHB continued to increase in the postpartum period.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Fatty acids (FFA) and b-hydroxybutyrate (BHB) are the two markers used to assess the severity of the negative energy balance. In a previous study including four commercial farms located in Italy and Greece, our group showed that these two markers are not well correlated during the transition period (Pilotto et al 2016). In fact, the concentration of free fatty acids in blood became maximal during calving and declined postpartum, while BHB continued to increase in the postpartum period.…”
Section: Introductionmentioning
confidence: 77%
“…Diets on all farms have been reported in detail in a previous study from our group (Pilotto et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplementing dairy cattle with adequate amounts of vitamin E and Se is thus now a widely-accepted practice. However, adequate levels of these micronutrients do not completely control oxidative stress around calving (3,6,27). Numerous studies in dairy cows (34) have shown that the plasma vitamin E concentration decreases gradually around parturition, reaching the lowest values around calving and then increasing gradually afterwards.…”
Section: Vitamin Ementioning
confidence: 99%